PENGEMBANGAN VIRTUAL TOUR DESA WISATA CARANGSARI, BADUNG - Kusuma Negara, I Made; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023), 2023)
The tourist village spread across the Badung district shows the impact of fluctuating visits. Travelers not only expect quick information but also expect information packaged in an attractive way. This research focuses on the development of a virtual tour of the potential tourist village of Carangsari in the Badung district into virtual reality media (VR). This study's data was gathered through library surveys, observations, and interviews with government officials, tourists, and local residents. The collected data will be grouped and presented according to the needs of the research, which will then be analyzed and synthesized descriptively. The development of the VR content of the tourist village of Carangsari is done by digging up the natural and cultural potential that exists, such as in tourism in Puri Carangsari, tracking tracks, traditional crafts, and agriculture in local communities.